FUNCTIONING OF THE NAMES OF KHOREZM MONUMENTS IN WRITTEN SOURCES - Shamsutdinova Galia Shamilevna (Western European Studies, 2024)
In this article, the names of Khorezm monuments have their own historical and cultural significance, which is necessary to understand the rich heritage of this ancient region. In written sources, these names serve as linguistic and symbolic signs that provide insight into the architectural, religious and social dynamics of Khorezm's past. By using these names in written sources, researchers, scholars and enthusiasts reveal the events, meanings and identities embedded in the monumental landscape of Khorezm
Keywords: researchers; written sources; texts; materials